Perceived Barriers of Physical Activity among School-going Adolescents - Sameena Ahmad; Mohammad Athar Ansari; Salman Khalil; Ali Jafar Abedi (Preventive Medicine: Research & Reviews)
Introduction: This study dives into physical activity (PA) level (PAL) and its barriers among school-going adolescents, focusing on an important stage where lifestyle decisions are shaped. Materials and Methods: The study was undertaken among 800 school-going adolescents between the age group of 12 and 14 years in high schools. The research enquired about the frequency and barriers of PA in a self-reported questionnaire, between July 2018 and June 2019. The collected data were analysed in SPSS 20.0. Results: The mean age of the students was 12 ± 0.81 years. The majority of the students were moderately physically active (53%), while 23% had high and 24% had low PALs. Males had higher PAL (56.3%), as compared to females (47.8%). Lack of energy for PA, academic priority and busy lesson schedules were found to have significant association (P < 0.05). Conclusion: In order to promote PA and guarantee a comprehensive approach to the health and well-being of adolescents, it is imperative that strategies including families, schools, communities and government commitment be implemented.